Evaluation of Preptin and other Biomarkers in Coronary Artery Disease Patients with and without Diabetes Mellitus - Yassen, Saja T.; Farhan, Layla O. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Preptin is an endocrine peptide with 34 amino acids. Conjugated with insulin, it is produced by β-cells from the pro-insulin-like growth factor 2 E-peptide. However, in addition to insulin, pancreatic hormone (Preptin) is released in response to elevated blood glucose levels. Preprint’s primary metabolic effect is to raise insulin synthesis, which is achieved through both an amplifying mechanism and a triggering route that is dependent on calcium signalling. Objectives: To determine the Preptin in patients with coronary artery disease (CAD) with and without Type 2 diabetes mellitus (T2DM). Methods: One hundred and twenty Iraqi participants between the ages of 40 and 60 years were enrolled (80 patients and 40 age-matched controls). The study took place between August and December 2023 at the Ibn Al-Bitar Centre for Cardiac Surgery in Baghdad, Iraq. The level of Preptin in patients with CAD with and without T2DM was evaluated. The biochemical tests performed on participants included fasting blood sugar (FBS), total cholesterol (TC), triglycerides (TG), low density lipoproteins (LDL), and very low-density lipoproteins (VLDL), high density lipoproteins (HDL), blood urea, serum creatinine, and uric acid. The waist-to-hip ratio (WHR) and body mass index (BMI) were also computed. There was a significance level below 0.05 using the Mann-Whitney tests. A non-parametric method and the Spearman’s rank coefficient were used to determine the significance of the correlation for the relationship between the two numerical variables. We determined the Preptin cut-off value by analysing the receiver operation characteristic (ROC) curve. Results: The CAD cases both with and without T2DM had a significantly higher serum Preptin than the control group. The levels of Preptin, HDL, and uric acid were significantly strongly correlated. The Preptin ROC curve showed a clear cut-off value (>601.71, >818.10, and >694.71) with the area under the curve (AUA) (0.973, 0.996, and 0.985), respectively, when calculated in three groups: CAD without T2DM, CAD with T2DM, and both CAD groups together compared with the controls. Conclusion: Preptin may serve as a predictive marker for the progression of declining heart function in people with T2DM. It also works well as a diagnostic tool to distinguish between patients with CAD and those without.